Pengolahan Limbah Cair Batik dengan Kombinasi Elektrokoagulasi dan Adsorpsi - Muchammad Kasyfurrahman Shidqi; Raden Kokoh Haryo P; Muhammad A. S. Jawwad (Jurnal Serambi Engineering, 2026)
The batik industry is one of Indonesia’s rapidly growing cultural and economic sectors. However, its production process generates wastewater containing high levels of synthetic dyes, total suspended solids (TSS), and chemical oxygen demand (COD), which can deteriorate water quality. This study aims to evaluate the effectiveness of the combined electrocoagulation–adsorption process in reducing dye, TSS, and COD concentrations in batik wastewater. The electrocoagulation process used aluminum electrodes with current variations of 1–5 A and contact times of 30–150 minutes, followed by adsorption using activated carbon as the adsorbent. The results showed that the combined process achieved excellent pollutant removal efficiency. Dye concentration decreased from 6742 Pt-Co to 93 Pt-Co, TSS from 5100 mg/L to 80 mg/L, and COD from 2432 mg/L to 39 mg/L, with overall removal efficiencies of 98–99%. The optimal condition was obtained at 5A and 150 minutes of reaction time. In conclusion, the electrocoagulation–adsorption combination is proven to be effective and environmentally friendly for reducing pollutant loads in batik wastewater.